2020
DOI: 10.5334/gh.403
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Diseases in Sub-Saharan Africa Compared to High-Income Countries: An Epidemiological Perspective

Abstract: Non-communicable diseases (NCDs) are the second common cause of death in sub-Saharan Africa (SSA) accounting for about 35% of all deaths, after a composite of communicable, maternal, neonatal, and nutritional diseases. Despite prior perception of low NCDs mortality rates, current evidence suggests that SSA is now at the dawn of the epidemiological transition with contemporary double burden of disease from NCDs and communicable diseases. In SSA, cardiovascular diseases (CVDs) are the most frequent causes of NCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
211
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(254 citation statements)
references
References 115 publications
9
211
1
Order By: Relevance
“…A majority of participants (72.6%) had at least one risk factor of metabolic syndrome. These findings are in line with many studies that have demonstrated a high prevalence of non-communicable diseases and their risk factors in some sub-Saharan African settings [33].…”
Section: Distribution Of Participants According the Number Of Risk Fasupporting
confidence: 92%
“…A majority of participants (72.6%) had at least one risk factor of metabolic syndrome. These findings are in line with many studies that have demonstrated a high prevalence of non-communicable diseases and their risk factors in some sub-Saharan African settings [33].…”
Section: Distribution Of Participants According the Number Of Risk Fasupporting
confidence: 92%
“…The rising burden of CVD morbidity and mortality in SSA has been reported to occur in younger age groups [1,37]. This, coupled with high levels of unawareness of risk factors and challenges with secondary prevention, calls for the evaluation of simple tools that can be used in routine screening for subjects with poor CVH in primary prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…ACS is a forgotten domain in sub-Saharan Africa (SSA) since it was historically believed to be uncommon [ 6 ]. However, in recent years, SSA has faced a rapid increase in IHD risk factors, including hypertension, diabetes, dyslipidemia, obesity, and physical inactivity augmented by rapid urbanization and globalization [ 7 ].…”
Section: Introductionmentioning
confidence: 99%